STRATEGI PEMBELAJARAN PENDIDIKAN JASMANI ADAPTIF BAGI ABK TUNAGRAHITA DAN TUNARUNGU: STUDI DI SLB KARISIDENAN PEKALONGAN - Kresnapati, Pandu; Fatkhu Royana, Ibnu; Hadi, Husnul; Wibisana, Muh Isna Nurdin (Journal of Physical Activity and Sports (JPAS), 2025)
This study aims to describe the learning process of Adaptive Physical Education for Children with Special Needs (ABK) with Mental Retardation and Deafness in Special Needs Schools (SLB) in the Pekalongan Residency area. Through a qualitative descriptive approach, data were collected using observation and interview methods with teachers and students, with subjects in this study being students with mental disability and deafness in 2 SLB N in the Pekalongan area. The results of the study indicate that the learning process has been carried out optimally according to the applicable curriculum. Teachers develop teaching modules and make adjustments to materials, media, and learning infrastructure. Modifications to learning aids are adjusted to the needs and abilities of students. Evaluation is carried out through formative and summative assessments. The study also highlights differences in behaviour between hyperactive and non-hyperactive students in participating in learning. The conclusion shows that adaptive physical education learning designed with appropriate strategies and approaches can increase the participation and independence of ABK students. The output of this study is a scientific article that has been accepted in a national journal indexed by SINTA.